The role of resistance exercise-induced local metabolic stress in mediating systemic health and functional adaptations: could condensed training volume unlock greater benefits beyond time efficiency? - Curovic, Ivan (Frontiers in Physiology, 2025)
The majority of “specialised” exercise configurations (e.g., supersets, drop sets, blood flow restriction) are being assessed as “shortcuts” to hypertrophy and strength improvements. However, these advanced training techniques may also offer significant benefits for systemic health and functional outcomes across recreational and clinical populations via locally induced metabolic responses. Stress-regulating mechanisms are known to enhance the body’s resilience by facilitating allostasis, the process of coordinating adaptive processes in reaction to stressors such as physical training. Yet, the role of the local metabolic stress provoked by resistance exercise has not gained much research attention despite its wide potential. Positive effects are not only linked to improved muscular endurance, hypertrophy and strength via primary and secondary mechanisms, but also to the release of myokines, hormones, microRNAs, immune factors, inflammatory substances and other endocrine molecules that initiate numerous health-promoting modifications on a systemic level. Resistance exercise strategies that maximise the local accumulation of metabolites are not well defined, although high volume, close proximity to failure and shorter rests seem to be a necessity. Additionally, blood flow restriction training provides a potent alternative for inducing local acidosis, thereby triggering several pathways associated with improved immunity and physical function even in remote muscle tissues. Future research is warranted to further explore advanced resistance training techniques, as these approaches may offer comparable benefits for physical and mental health to those seen with other forms of exercise such as high-intensity interval training and heavy resistance training.